Participation of Azerbaijan in the Environmental Activities of the UNEP, the Council of Europe and the CIS - Adel Ilsijarovich, Abdoulin; Parviz Arif Ogli, Gasanov; Galina Georgievna, Shinkaretskaia; Ksenia Borisovna, Valiullina (International Journal of Criminology and Sociology, 2022)
Ecosystems of the Azerbaijan Republic have a lot of unique characteristics that demand the special focus in the context of the environmental protection. Taking into account their importance, it is necessary to apply whole potential of international cooperation including institutional dimension. The purpose of the article is to describe the characteristics of the participation of the Azerbaijan Republic in the activities of the United Nations Environmental Programme (UNEP), the Council of Europe and the Commonwealth of Independent States (CIS) on the protection of environment. As the basic method of research, the author proposes the method of legal comparison. The generalization of the results of the cooperation of the Azerbaijan Republic allows to define the respective traits of interaction with every international organization from the abovementioned list. They are determined by the purposes, functions, opportunities and mechanisms of interaction in every respective case. For example, the Azerbaijan Republic focuses its attention on development and improvement of the environmental management mechanism and resilience to natural and human-induced hazards. At the same time, the environmental cooperation of the Azerbaijan Republic and the Council of Europe is based on the participation in the regional conventional mechanisms and formation of the necessary conditions for the realization of the environmental rights of humans, including the activity of the European Court of Human Rights. Additionally, based on the examples of cooperation of the Azerbaijan Republic with the UNEP, the Council of Europe and the CIS, the author reveals the presence of dynamic, complex and systemic approach to cooperation with the aforementioned international organizations. The global, comprehensive nature of the environmental challenges facing the world community contributes to the formation of a new worldview and practice of international economic interaction between the participants of the world economy, based on the support of the strong States to the weak in ensuring the most important, generally significant tasks of the economy and the environment.